The Effect of Motivation and Health Officer’s Performance on The Service Quality in Handling Stunting at Pabuaran Public Health Center Pabuaran Sub-District Sukabumi Regency - Atang Priatna; Munandi Saleh; Erry Sunarya (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to determine the effect of motivation and health service officer’s performance on the service quality in handling stunting at the Pabuarann Public Health Center, Pabuaran sub-district, Sukabumi Regency. The sample in this study amounted to 130 people. The data collection technique uses a questionnaire. The data analysis technique uses multiple regression analysis on SPSS version 22. The results of hypothesis testing show that work motivation has a significant positive effect on the service quality in handling stunting; Officer performance has a significant positive effecr on service qualitys. Simultaneously, work motivation and officer performance have a significant effect on the service quality in handling stunting with a variance proportion of 0.626 or around 62.6%. This means that 62.6% of the variation in service quality variables is related to the independent variables in this research, while the remaining 37.4% of the variation in service quality is related to other variables outside this research. Through this research, it can be seen that to achieve excellent service quality, strategies can be implemented to increase work motivation and officer performance.